The Audit “Dressed” in Law, or Some Aspects of the Auditor’s Responsibility in Ukraine - REDKOО. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2021)
An evidence of the auditing activities’ globalization is the unification of technical rules and norms of auditing practices across countries, including international requirements to the quality of audit, taking form of standards or recommendations or legal acts. But the legal responsibility of an auditor before customers remains to be in the national jurisdictions. The article highlights the peculiarities in implementing the legal responsibility of an auditor by case of Ukraine. In the legal framework of the Ukrainian audit, namely in the Law of Ukraine “Audit of Financial Statements and Auditing Activities” from 21.12.2017, there appeared a new notion, “professional responsibility”. Its essence and specifics of usage in the Ukrainian auditing practice regulated by the above law are highlighted by analyzing the categories of customers of auditing services, which can be potential claimants on auditors for the allegedly poor quality of services; categories of legally fixed violations for which an auditor can be held accountable in court; categories of legally fixed duties of auditors and auditing entities. Results of the study lead to the conclusion that the auditing activities in Ukraine have not been established yet, because the auditing business has to be run in a blurred legal framework, with the legal accountability of an auditor specified by a large number of legal acts setting various priorities and regulating various working aspects of auditors and auditing entities. The current Law of Ukraine “Audit of Financial Statements and Auditing Activities”, apart from failing to remove these drawbacks, seems to be designed to turn an independent auditor into a regulated tool of government control over auditing entities, with overlooking the fact that the audit is a business activity. Recommendations on improvements of the current law regulating the audit in Ukraine in order to strengthen its capacities and increase the demand for auditing services from business enterprise and government sector are given.